Role of Media in Coverage and Reporting of Child Abuse Cases - Habib, Ghulam; Urfan Ullah, Muhammad; Khanum, Taiyyaba; Khan, Ayesha (Riviera Publishing, 2023)
Child abuse is arguably one of the most debated publics/social policy areas. Thus, the need for systematic data is not only for recognizing child protection issues but also for formulating and implementing policy responses and practices in Pakistan. This study aims to analyze the role of the media in the research and reporting of child abuse cases. The method used in this study is to use media framing theory to conduct quantitative investigations using content analysis. Media coverage of child abuse can help communities understand issues around child abuse and neglect and interact constructively with children's rights. Using media as a reporting, representation, and advocacy tool will increase public knowledge about perpetrators and aid in preventing child abuse. However, there are shortcomings in structures and institutions that can cause children suffering. It needs cooperation from government agencies and civil society to improve child protection from maltreatment and carelessness. Therefore, the role of the media as a component of a more extensive system designed to protect children is crucial. Child sexual abuse can be reduced in the country by enacting strong anti-child sexual abuse laws. By affirming the country's commitment, providing legal protection, increasing public awareness, increasing the effectiveness of law enforcement. With clear laws in place, police and the justice system can act on child sexual abuse cases more quickly and decisively. This can provide a deterrent effect to perpetrators and prevent similar crimes in the future.